The Role of Physical Activity in Enhancing and Preserving Skin Health - Szatkowska, Julia; Teofilak, Mateusz; Śpiołek, Olga; Siwiec, Jan; Smyl, Natalia; Kędziora, Franciszek; Wąsowicz, Agnieszka; Słowikowska, Aleksandra; Sztyler-Krąkowska, Marcelina; Fabian, Dariusz (Journal of Education, Health and Sport, 2024)
Introduction: Interest in the relationship between physical activity and skin health has grown significantly in recent years. Both scientific literature and media platforms highlight the influence of exercise on skin vitality, with social media often emphasizing its aesthetic benefits. Scientific studies, however, focus on mechanisms like improved circulation, enhanced collagen production, and reduced inflammation. This review aims to analyze the impact of physical activity on skin health, examining its benefits and potential drawbacks while providing a comprehensive understanding of the biological processes involved. Aim of the study: The study seeks to review scientific literature to evaluate the effects of physical exercise on skin health and condition. Materials and methods: The authors conducted a review of scientific literature using databases such as PubMed, ScienceDirect, UpToDate, and Google Scholar. Articles from 2003 to 2024 were analyzed with keywords including physical activity and skin health, exercise and dermatology, skin metabolism, and exercise benefits for the skin. Only studies relevant to the relationship between physical activity and skin health were included. Results and conclusions: Physical activity significantly benefits skin health by boosting collagen production, improving circulation, and reducing cortisol levels, resulting in a radiant and youthful complexion. However, risks such as barrier damage, increased sebum production, and infections must be managed. Personalized skincare routines emphasizing cleansing, hydration, and protection against environmental factors are essential for individuals engaging in regular exercise.